2020
DOI: 10.1101/2020.03.02.972901
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic cell wall modifications in brassicas during clubroot disease

Abstract: 15 Biotic interactions of plants and microbial pathogens can cause drastic changes in cell wall 16 composition in response to developmental reprogramming caused as consequence of an 17 infection. Clubroot disease, caused by the biotrophic plant pathogen Plasmodiophora brassicae 18 (Phytomyxea, Rhizaria), is the economically most important disease of Brassica crops 19 worldwide. The disease is best known by the characteristic hypertrophied roots (root galls, 20 clubroots). Amongst a series of physiological chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…A general overview on the expression of genes whose products are involved in cell wall loosening or degradation during late stages of gall development in Arabidopsis shows that only a limited number of genes are induced and a large number of them are in fact downregulated ( Supplementary Figure S4 ). Recent work of Badstöber et al (2020) showed that a large number of PME gene transcripts increased in mature galls in P. brassicae -infected kohlrabi ( Brassica oleracea ). They also found increased expression of other genes whose products may be involved in cell expansion ( XTH or EXP ) or degradation ( GH9 cellulases ) processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A general overview on the expression of genes whose products are involved in cell wall loosening or degradation during late stages of gall development in Arabidopsis shows that only a limited number of genes are induced and a large number of them are in fact downregulated ( Supplementary Figure S4 ). Recent work of Badstöber et al (2020) showed that a large number of PME gene transcripts increased in mature galls in P. brassicae -infected kohlrabi ( Brassica oleracea ). They also found increased expression of other genes whose products may be involved in cell expansion ( XTH or EXP ) or degradation ( GH9 cellulases ) processes.…”
Section: Discussionmentioning
confidence: 99%
“…These events have a vast impact on tensions at the organ level; therefore, regulation of cell wall dynamics involves appropriate control of the cell adhesion/cell separation balance that is highly dependent on pectin status, and secondary cell wall modifications ( Jarvis et al, 2003 ). Transcriptomic and proteomic studies of clubroot disease have identified extensive changes in host genes and proteins involved in cell wall synthesis and turnover ( Devos et al, 2006 ; Badstöber et al, 2020 ). Additionally, host cell wall degradation or thickening has been documented at the microscopic level ( Donald et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…While pectin plays an important role in cell expansion, adhesion, strength, and porosity, lignification protects cell wall polysaccharides from degradation [ 253 ]. Down-regulation of genes involved in the biosynthesis of cellulose, hemicellulose, pectin, callose, and lignin decreased root cell wall rigidity and stability of the clubroot infected cells of Brassica plants [ 254 ]. On the contrary, enzymes responsible for degrading these elements were up-regulated in clubroots.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…However, to protect the plant cells from excessive degradation from pectinase, host plants produce enzyme-inhibiting enzymes, such as PMEIs (PME-inhibitor) and PGIPs (PG-inhibiting protein). In the clubroots of Brassica plants, the genes coding these inhibitors were down-regulated [ 254 ]. Plant cell-wall-degrading enzymes (CWDEs) play an important role in loosening and the breakdown of cell wall components [ 255 ] and establishment of pathogens [ 256 ].…”
Section: Transcriptomicsmentioning
confidence: 99%
See 1 more Smart Citation